Effect of congruence between medium of instruction and testing in assessing students' achievement in general college chemistry - Rigonan, Evalina Gabay (Animo Repository, 1995)
This study determines the differential effects of the congruence or non-congruence between medium of instruction and testing on students' achievement.The language of instruction used was English and mixed (English-Filipino) and the medium of testing was also in English and mixed. Items in the achievement test include: atomic structure, chemical bonding and stoichiometry.This study was conducted over a 4-week period during the second semester of school year 1993-1994. First year engineering students enrolled in General Chemistry 1 at Mariano Marcos State University, Batac campus, grouped into experimental and control groups were the subjects of the study. The study utilized a quasi-experimental factorial group design. The data gathered were analyzed using the Analysis of Covariance at 0.05 level of significance.The study concluded that the language of instruction has no effect on the language of testing. Students are not affected by the language used in teaching when it comes to taking the test in English or mixed language, As regards the language used in testing, the achievement of students who took the test where the language used is mixed is higher.